Efficient chemical liquid phase coating method of metal soft magnetic powder and application

Through the efficient chemical liquid phase coating method, the fluidized bed and atomization technology are used to form a uniform Al2O3 coating layer, which solves the problems of complex coating methods, low efficiency and uneven coating layers in the prior art, and realizes efficient and uniform coating of metal soft magnetic powder, which is suitable for high-frequency and high-temperature applications.

CN119560254AActive Publication Date: 2025-03-04HUAZHONG UNIV OF SCI & TECH

Patent Information

Application Number
CN202411690961.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-04
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing metal soft magnetic powder coating methods are complex, inefficient, and uneven coating layers, making it difficult to meet the needs of high frequency and low cost production.

Method used

Using high-efficiency chemical liquid phase coating method, the aluminum isopropoxide solution is uniformly atomized through fluidized bed technology and atomization nozzle, and fully reacted with metal soft magnetic powder to form a uniform Al2O3 coating layer. By combining calcination and resin binder, a uniform and efficient soft magnetic composite material is prepared.

Benefits of technology

It realizes uniform and efficient coating of metal soft magnetic powder, forming a aluminum oxide coating with controllable thickness and uniform coating, reducing production costs and improving coating efficiency, and is suitable for high-frequency and high-temperature application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560254A_ABST
    Figure CN119560254A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient chemical liquid phase coating method of metal soft magnetic powder and application, and belongs to the technical field of preparation of soft magnetic materials, aluminum isopropoxide is dissolved to form a coating precursor solution, and an Al2O3 insulation coating layer is formed on the surface of the fluidized metal soft magnetic powder after hydrolysis and dehydration reactions. The aluminum isopropoxide is dissolved to form gel, the gel is uniformly mixed with the fluidized metal soft magnetic powder, dried gel can be formed on the surface of the metal soft magnetic powder after high-temperature airflow drying, and the dried gel is further calcined and dehydrated to form the high-insulativity Al2O3 coated metal soft magnetic powder. The method can be widely applied to surface insulation coating of the metal soft magnetic powder, has the characteristics of controllable coating layer thickness, simplicity, rapidness and high coating efficiency, and meets the requirements of industrial production such as large-scale, low-cost, safe and environment-friendly industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic material preparation, and more specifically, relates to a high-efficiency chemical liquid phase coating method for metal soft magnetic powder and application thereof. Background Art

[0002] Soft magnetic composite materials (metal powder cores, SMCs) are generally made of insulating magnetic powder. They have obvious advantages over traditional silicon steel sheets and soft ferrites due to their magnetic isotropy, high Curie temperature, low loss, distributed air gap and easy molding and manufacturing. They have become a key material for magnetic components in high-frequency and high-power application scenarios.

[0003] The insulating coating on the surface of metal soft magnetic powder is the key to achieving high frequency and low eddy current loss in SMCs. Therefore, insulating coating is crucial for the high-frequency development of soft magnetic composite materials. In the production process of soft magnetic composite materials, it is necessary to improve the uniformity of the coating layer of magnetic powder, and at the same time, the coating process is required to be low-cost and high-efficiency. Therefore, it is urgent to develop a low-cost and efficient soft magnetic powder coating method.

[0004] There are many related research reports on the coating methods of metal soft magnetic powders. From the perspective of the material composition of the coating layer, it is currently mainly divided into two categories: organic coating and inorganic coating. Among them, thermosetting polymer materials such as epoxy resin, phenolic resin, silicone resin, etc. are more widely used under low-temperature curing conditions; while phosphates formed by surface phosphating reactions or inorganic coatings such as SiO2 and Al2O3 formed by other reactions generally meet the application requirements of high-temperature annealing processes.

[0005] In general, although the organic coating layer can effectively wrap the magnetic powder and fill the gaps between the magnetic powders, its poor high temperature tolerance makes it have the risk of decomposition and failure in harsh environments. The inorganic coating layer has better high temperature tolerance, but the general preparation method is more complicated. These methods also have some problems such as environmental unfriendliness, high cost, low coating efficiency, and uneven coating layer. Summary of the invention

[0006] In view of the above defects or improvement needs of the prior art, the present invention provides a high-efficiency chemical liquid phase coating method and application of metal soft magnetic powder, thereby solving the technical problems of the existing preparation method being relatively complicated, the coating efficiency being low, and the coating layer being uneven.

[0007] To achieve the above object, according to one aspect of the present invention, a high-efficiency chemical liquid phase coating method for metal soft magnetic powder is provided, the method comprising the following steps:

[0008] Placing the powder to be coated in the reaction chamber, and introducing a fluidizing gas source into the reaction chamber to uniformly fluidize the powder in the reaction chamber;

[0009] Dissolving a metal compound or an organic compound in a solvent to form a coating precursor solution, spraying the atomized precursor solution into a reaction chamber and allowing the atomized precursor solution to fully react with the powder to be coated, thereby obtaining a surface-modified metal soft magnetic powder;

[0010] calcining the surface-modified soft magnetic powder to obtain a coated magnetic powder with a core-shell structure of the soft magnetic powder, and mixing the coated magnetic powder with a resin binder to form granules and then pressing to obtain a green body of a soft magnetic composite material;

[0011] The metal soft magnetic composite material green body is subjected to heat treatment, and the metal soft magnetic composite material is obtained after completing heating curing or annealing treatment.

[0012] Preferably, the metal compound includes aluminum isopropoxide, pseudo-boehmite white powder, aluminum sec-butoxide, magnesium acetate tetrahydrate or sodium silicate nonahydrate; the organic compound includes ethyl orthosilicate or tetrabutyl titanate;

[0013] The purity of aluminum isopropoxide, pseudo-boehmite and aluminum sec-butoxide is greater than 99%, and the aluminum content is between 5% and 30%; the purity of ethyl orthosilicate, magnesium acetate tetrahydrate and sodium silicate nonahydrate is greater than 98%.

[0014] Preferably, the solvent includes a single organic solvent or a mixed solvent of deionized water, methanol, ethanol, glycerol, isopropanol, and toluene.

[0015] Preferably, the metallic soft magnetic powder comprises at least one of carbonyl iron powder, Fe-Ni-Mo alloy powder, Fe-Ni alloy powder, Fe-Co alloy powder, Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Si-Cr alloy powder, Fe-based amorphous alloy powder, Ni-based amorphous alloy powder, Co-based amorphous alloy powder and Fe-based nanocrystalline powder.

[0016] Preferably, the temperature of the fluidizing gas source is 50°C to 600°C, and the flow rate of the gas source is 4m 3 / min~50m 3 / min, the air flow speed is 0.4m / s~10m / s.

[0017] Preferably, the calcination temperature range is 400° C. to 1000° C., and the calcination time is 1 h to 3 h.

[0018] Preferably, the coating precursor solution is drawn into an atomizing device through a suction device, and forms a precursor solution spray after passing through the atomizing device.

[0019] Preferably, the rotation speed of the suction device is 2 r / min to 100 r / min, and the air pressure of the atomization device is 0.1 MPa to 10 MPa.

[0020] According to another aspect of the present invention, there is provided a metal soft magnetic composite material prepared by a high-efficiency chemical liquid phase coating method for metal soft magnetic powder and its application in an integrally formed inductor or metal soft magnetic powder core.

[0021] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects compared with the prior art:

[0022] 1. The high-efficiency chemical liquid phase coating method of metal soft magnetic powder proposed by the present invention adopts the powder fluidization method and utilizes fully atomized aluminum isopropoxide solution to coat and modify the surface of metal soft magnetic powder. It is a new idea and new process method for uniform and efficient coating of metal soft magnetic powder. Aluminum isopropoxide is also called organic aluminum. Its hydrolysis and polycondensation process can effectively form a network structure. It is uniformly mixed with metal powder and can form an Al2O3 coating layer on the surface of soft magnetic powder after calcination and dehydration. The process of preparing aluminum oxide coating layer by this method has controllable thickness, uniform coating, simple and fast operation, and can meet the needs of industrial production such as large-scale, low-cost, safe and low-pollution.

[0023] 2. The present invention proposes a high-efficiency chemical liquid phase coating method for metal soft magnetic powder. This method can form a dry gel coating layer by drying at 80°C, and then further calcining according to the heat treatment temperature required by the metal powder. The dry gel will be converted into alumina coating layers of different phases at different temperatures, which greatly expands the application temperature range of the method.

[0024] 3. The efficient chemical liquid phase coating method for metallic soft magnetic powder proposed in the present invention uses a fluidized bed to uniformly fluidize the powder, and combines an atomizing nozzle to uniformly atomize the precursor solution. The uniformly fluidized powder and the atomized precursor solution are in more uniform contact, so a more uniform Al2O3 coating layer is obtained after coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic structural diagram of a coating device for a high-efficiency chemical liquid phase coating method of a metal soft magnetic powder according to the present invention;

[0026] Figure 2 It is a SEM picture of Fe-Cr-Si-BC soft magnetic powder after coating by the high-efficiency chemical liquid phase coating method of the metal soft magnetic powder of the present invention;

[0027] Figure 3 is a SEM result image of the metal soft magnetic powder prepared in Example 1 of the present invention at different precursor concentrations;

[0028] Figure 4 1 is a powder EDS result diagram of the soft magnetic metal powder prepared in Example 1 of the present invention at different precursor concentrations;

[0029] Figure 5 1 is a graph showing the powder resistivity of the soft magnetic metal powder obtained in Example 1 of the present invention at different precursor concentrations;

[0030] Figure 6 1 is a graph showing the powder resistivity of the carbonyl iron powder obtained in Example 3 of the present invention before and after coating;

[0031] Figure 7 is a cross-sectional TEM image of the coated soft magnetic metal powder obtained in Example 1 of the present invention;

[0032] Figure 8 is an EDS result diagram of the metallic soft magnetic powder obtained in Example 8 of the present invention;

[0033] Fig. 9 This is the EDS result diagram of the metallic soft magnetic powder prepared in Example 9 of the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0035] The present invention provides a high-efficiency chemical liquid phase coating method for metal soft magnetic powder, comprising the following steps:

[0036] (1) dissolving the organoaluminum in a suitable solvent to form a coating precursor solution;

[0037] Specifically, the organic aluminum is white powder such as aluminum isopropoxide, pseudo-boehmite, and other common aluminum sols such as aluminum sec-butoxide, with a purity greater than 99% and an aluminum content of about 5% to 30%. The solvent is common organic solvents such as deionized water, methanol, ethanol, glycerol, isopropanol, toluene, and mixed solvents thereof;

[0038] (2) The coating precursor solution is extracted by a suction device, and after passing through an atomization device, the coating precursor forms a uniform precursor spray in the reaction chamber.

[0039] Specifically, the suction device is generally a peristaltic pump, aspirator or other device with controllable liquid transport capability; the atomization device is generally an ultrasonic atomizer, a pneumatic atomizer, a mechanical atomizer, an electric atomizer or other common liquid spray devices; the reaction chamber is a cylindrical reaction container, which is the coating reaction area of ​​the fluidized powder.

[0040] (3) Placing the powder to be coated into the reaction chamber of step (2), and adjusting the fluidizing gas source of the reaction chamber so that the powder is uniformly fluidized in the reaction chamber.

[0041] Specifically, the fluidizing gas source is a high-speed hot gas flow that passes through the reaction chamber from bottom to top, so that the powder is uniformly fluidized in the reaction chamber. The fluidizing gas source has a certain temperature, so that the coating precursor solution can solidify on the powder surface more quickly. There is an agitator at the bottom of the reaction chamber to prevent the powder from accumulating in the corners of the reaction chamber.

[0042] (4) Turn on the suction device and the atomization device, and when all the precursor solution enters the reaction chamber, the reaction is completed, and a surface-modified metal soft magnetic powder is obtained.

[0043] (5) After the modified metal soft magnetic powder is calcined at high temperature, a coated magnetic powder with a metal soft magnetic powder@Al2O3 core-shell structure is obtained.

[0044] (6) Add a resin binder to the coated magnetic powder in step (5), mix and granulate, and then press into shape.

[0045] (7) heat treating the green body of the metal soft magnetic composite material obtained in step (6) to obtain the metal soft magnetic composite material after completing heating curing or annealing treatment.

[0046] To further explain, in step (4), the temperature of the reaction chamber can be raised to 600° C. or higher, so that the subsequent calcination step can be omitted and the alumina-coated metal soft magnetic powder can be directly obtained.

[0047] To further explain, the solvent is generally deionized water, and organic solvents such as methanol, ethanol, propanol, isopropanol, toluene, etc. can also be added to the solvent to adjust its reaction characteristics. The mass ratio of the organic solvent to deionized water is 1:10 to 10:1.

[0048] To further illustrate, aluminum isopropoxide accounts for 0.1% to 10% of the total mass of the solution.

[0049] To further illustrate, aluminum isopropoxide accounts for 0.1% to 20% of the mass of the metal soft magnetic powder.

[0050] The technical solution of the present invention is further illustrated by specific embodiments below.

[0051] Example 1

[0052] This embodiment provides a high-efficiency chemical liquid phase coating method for metal soft magnetic powder, which comprises the following steps:

[0053] (1) Weigh 36 mL of deionized water and 100 mL of ethanol solution, mix them evenly, and add 10 g of aluminum isopropoxide to obtain an aluminum isopropoxide precursor solution.

[0054] (2) Weigh 1000 g of Fe-Cr-Si-BC amorphous soft magnetic powder and place it at the bottom of the reaction chamber. Set the fluidizing gas flow temperature to 80°C, turn on the peristaltic pump and atomizing nozzle to ensure continuous reaction.

[0055] (3) The xerogel-coated Fe-Cr-Si-BC powder was placed in a muffle furnace and calcined at 500° C. for 1 h under a nitrogen atmosphere to obtain the coated powder.

[0056] (4) Take 100 g of the coated Fe-Cr-Si-BC powder and stir it thoroughly with 2 g of resin (20 ml of acetone solvent) solution. After the solvent evaporates completely, sieve it to obtain Fe-Cr-Si-BC alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0057] (5) The granulated powder is pressed at 600 MPa to obtain a soft magnetic composite material green body.

[0058] (6) The green body was cured in an air atmosphere at 200° C. for 1 hour to obtain a soft magnetic composite material sample.

[0059] Example 2

[0060] This embodiment provides a high-efficiency chemical liquid phase coating method for metal soft magnetic powder, which comprises the following steps:

[0061] (1) Weigh 36 mL of deionized water and 100 mL of ethanol solution, mix them evenly, and add 10 g of aluminum isopropoxide to obtain an aluminum isopropoxide precursor solution.

[0062] (2) Weigh 1000 g of Fe-Cr-Si-BC amorphous soft magnetic powder and place it at the bottom of the reaction chamber. Set the fluidizing gas flow temperature to 80°C, turn on the peristaltic pump and atomizing nozzle to ensure continuous reaction.

[0063] (3) The xerogel-coated Fe-Cr-Si-BC powder was placed in a muffle furnace and calcined at 500° C. for 1 h under a nitrogen atmosphere to obtain the coated powder.

[0064] (4) Take 100 g of the coated and modified Fe-Cr-Si-BC powder and 2 g of resin (20 ml of acetone solvent) solution and stir them thoroughly. After the solvent evaporates completely, sieve it to obtain Fe-Cr-Si-BC alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0065] (5) The granulated powder is pressed at 2000 MPa to obtain a soft magnetic composite material green body.

[0066] (6) The green body was annealed in a nitrogen atmosphere at 500°C for 1 hour to obtain a soft magnetic composite material sample.

[0067] Example 3

[0068] This embodiment provides a high-efficiency chemical liquid phase coating method for metal soft magnetic powder, which comprises the following steps:

[0069] (1) Weigh 38 mL of deionized water and 100 mL of ethanol solution, mix them evenly, and add 12 g of aluminum isopropoxide to obtain an aluminum isopropoxide precursor solution.

[0070] (2) Weigh 1000 g of carbonyl iron powder and place it at the bottom of the reaction chamber. Set the fluidizing gas flow temperature to 80° C. and start the peristaltic pump and atomizing nozzle to ensure continuous reaction.

[0071] (3) The xerogel-coated Fe-Cr-Si-BC powder was placed in a muffle furnace and calcined at 500° C. for 1 h under a nitrogen atmosphere to obtain the coated powder.

[0072] (4) Take 100 g of the coated and modified Fe-Cr-Si-BC powder and 2 g of resin (20 ml of acetone solvent) solution and stir them thoroughly. After the solvent evaporates completely, sieve it to obtain Fe-Cr-Si-BC alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0073] (5) The granulated powder is pressed at 600 MPa to obtain a soft magnetic composite material green body.

[0074] (6) The green body was cured in an air atmosphere at 200° C. for 1 hour to obtain a soft magnetic composite material sample.

[0075] Example 4

[0076] This embodiment provides a high-efficiency chemical liquid phase coating method for metal soft magnetic powder, which comprises the following steps:

[0077] (1) Weigh 38 mL of deionized water and 100 mL of ethanol solution, mix them evenly, and add 12 g of aluminum isopropoxide to obtain an aluminum isopropoxide precursor solution.

[0078] (2) Weigh 1000 g of carbonyl iron powder and place it at the bottom of the reaction chamber. Set the fluidizing gas flow temperature to 80° C. and start the peristaltic pump and atomizing nozzle to ensure continuous reaction.

[0079] (3) Weigh 1000 g of Fe-Cr-Si-BC powder and place it at the bottom of the reaction chamber. Set the fluidizing gas temperature to 80 °C and start the peristaltic pump and atomizing nozzle to ensure continuous reaction.

[0080] (3) The two powders coated with the dry gel were placed in a muffle furnace respectively and calcined at 500° C. for 1 h under a nitrogen protective atmosphere to obtain coated powders.

[0081] (4) Take 50 g of the coated and modified Fe-Cr-Si-BC powder and 50 g of the carbonyl iron powder, respectively, and stir them thoroughly with 2 g of resin (20 ml of acetone solvent) solution. After the solvent evaporates completely, sieve them to obtain powder granules with a particle size range of 40 mesh to 200 mesh.

[0082] (5) The granulated powder is pressed at 600 MPa to obtain a soft magnetic composite material green body.

[0083] (6) The green body was cured in an air atmosphere at 200° C. for 1 hour to obtain a soft magnetic composite material sample.

[0084] Example 5

[0085] This embodiment provides a high-efficiency chemical liquid phase coating method for metal soft magnetic powder, which comprises the following steps:

[0086] (1) Weigh 38 mL of deionized water and 100 mL of ethanol solution, mix them evenly, and add 12 g of aluminum isopropoxide to obtain an aluminum isopropoxide precursor solution.

[0087] (2) Weigh 1000 g of carbonyl iron powder and place it at the bottom of the reaction chamber. Set the fluidizing gas flow temperature to 500° C. and start the peristaltic pump and atomizing nozzle to ensure continuous reaction.

[0088] (3) Take 100 g of the coated and modified Fe-Cr-Si-BC powder and stir it thoroughly with 2 g of resin (20 ml of acetone solvent) solution. After the solvent evaporates completely, sieve it to obtain Fe-Cr-Si-BC alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0089] (4) The granulated powder is pressed at 600 MPa to obtain a soft magnetic composite material green body.

[0090] (5) The green body was cured in an air atmosphere at 200° C. for 1 hour to obtain a soft magnetic composite material sample.

[0091] Example 6

[0092] This embodiment provides a high-efficiency chemical liquid phase coating method for metal soft magnetic powder, which comprises the following steps:

[0093] (1) Weigh 38 mL of deionized water and 100 mL of isopropanol solution, mix them evenly, and add 12 g of aluminum isopropoxide to obtain an aluminum isopropoxide precursor solution.

[0094] (2) Weigh 1000 g of Fe-Cr-Si-BC powder and place it at the bottom of the reaction chamber. Set the fluidizing gas temperature to 80 °C, and start the peristaltic pump and atomizing nozzle to ensure continuous reaction.

[0095] (3) The xerogel-coated Fe-Cr-Si-BC powder was placed in a muffle furnace and calcined at 500° C. for 1 h under a nitrogen atmosphere to obtain the coated powder.

[0096] (4) Take 100 g of the coated and modified Fe-Cr-Si-BC powder and 2 g of resin (20 ml of acetone solvent) solution and stir them thoroughly. After the solvent evaporates completely, sieve it to obtain Fe-Cr-Si-BC alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0097] (5) The granulated powder is pressed at 2000 MPa to obtain a soft magnetic composite material green body.

[0098] (6) The green body was annealed in a nitrogen atmosphere at 500°C for 1 hour to obtain a soft magnetic composite material sample.

[0099] Example 7

[0100] This embodiment provides a high-efficiency chemical liquid phase coating method for metal soft magnetic powder, which comprises the following steps:

[0101] (1) Weigh 38 mL of deionized water and 100 mL of isopropanol solution, mix them evenly, and add 12 g of aluminum sec-butoxide to obtain an aluminum sec-butoxide precursor solution.

[0102] (2) Weigh 1000 g of Fe-Cr-Si-BC powder and place it at the bottom of the reaction chamber. Set the fluidizing gas temperature to 80 °C, and start the peristaltic pump and atomizing nozzle to ensure continuous reaction.

[0103] (3) The xerogel-coated Fe-Cr-Si-BC powder was placed in a muffle furnace and calcined at 500° C. for 1 h under a nitrogen atmosphere to obtain the coated powder.

[0104] (4) Take 100 g of the coated and modified Fe-Cr-Si-BC powder and 2 g of resin (20 ml of acetone solvent) solution and stir them thoroughly. After the solvent evaporates completely, sieve it to obtain Fe-Cr-Si-BC alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0105] (5) The granulated powder is pressed at 2000 MPa to obtain a soft magnetic composite material green body.

[0106] (6) The green body was annealed in a nitrogen atmosphere at 500°C for 1 hour to obtain a soft magnetic composite material sample.

[0107] Example 8

[0108] This embodiment provides a high-efficiency chemical liquid phase coating method for metal soft magnetic powder, which comprises the following steps:

[0109] (1) Weigh 80 mL of deionized water and 160 mL of ethanol solution, mix them evenly, and add 20 mL of tetraethyl orthosilicate thereto to obtain a tetraethyl orthosilicate precursor solution.

[0110] (2) Weigh 2000 g of Fe-Si powder and place it at the bottom of the reaction chamber. Set the fluidizing gas temperature to 80°C, and start the peristaltic pump and atomizing nozzle to ensure continuous reaction.

[0111] (3) The Fe-Si powder coated with the dry gel was placed in a muffle furnace and calcined at 500° C. for 1 h under a nitrogen protective atmosphere to obtain a coated powder.

[0112] (4) Take 100g of the coated and modified Fe-Si powder and 2g of resin (20ml of acetone solvent) solution and stir them thoroughly. After the solvent evaporates completely, sieve it to obtain Fe-Cr-Si-BC alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0113] (5) The granulated powder is pressed at 2000 MPa to obtain a soft magnetic composite material green body.

[0114] (6) The green body was annealed in a nitrogen atmosphere at 700°C for 1 hour to obtain a soft magnetic composite material sample.

[0115] Example 9

[0116] This embodiment provides a high-efficiency chemical liquid phase coating method for metal soft magnetic powder, which comprises the following steps:

[0117] (1) Weigh 60 mL of deionized water and 200 mL of ethanol solution, mix them evenly, and add 40 g of magnesium acetate tetrahydrate to obtain a magnesium acetate tetrahydrate precursor solution.

[0118] (2) Weigh 2000 g of Fe-Si-Cr powder and place it at the bottom of the reaction chamber. Set the fluidizing gas temperature to 60° C. and start the peristaltic pump and atomizing nozzle to ensure continuous reaction.

[0119] (3) The Fe-Si-Cr powder coated with the dry gel was placed in a muffle furnace and calcined at 500° C. for 1 h under a nitrogen protective atmosphere to obtain a coated powder.

[0120] (4) Take 100g of the coated and modified Fe-Si powder and 2g of resin (20ml of acetone solvent) solution and stir them thoroughly. After the solvent evaporates completely, sieve it to obtain Fe-Cr-Si-BC alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0121] (5) The granulated powder is pressed at 658 MPa to obtain a soft magnetic composite material green body.

[0122] (6) The green body was cured at 150°C for 2 hours to obtain a soft magnetic composite material sample.

[0123] Comparative Example 1

[0124] This embodiment provides a method for preparing the above-mentioned metal soft magnetic composite material, which comprises the following steps:

[0125] (1) Weigh 0.6 g of phosphoric acid in 20 ml of ethanol and disperse by ultrasonic until it is completely dissolved to obtain a phosphoric acid passivation solution.

[0126] (2) Weigh 100 g of Fe-Cr-Si-BC amorphous soft magnetic powder and place it in a phosphoric acid passivation solution. Stir it in a water bath at 65° C. until it is completely dry to obtain a surface-coated modified Fe-Cr-Si-BC amorphous soft magnetic powder.

[0127] (3) The coated and modified Fe-Cr-Si-BC amorphous soft magnetic powder is fully stirred with 2g of resin (20ml of acetone solvent) solution, and after the solvent is completely evaporated, the powder is sieved to obtain Fe-Cr-Si-BC alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0128] (4) The granulated powder is pressed at 600 MPa to obtain a soft magnetic composite material green body.

[0129] (5) The green body was annealed in air atmosphere at 200°C for 1 hour to obtain a soft magnetic composite material sample.

[0130] The schematic diagram of the coating equipment used in the present invention is as follows Figure 1 As shown, Figure 2 The SEM images of the powders before and after coating in Example 1 are compared. Figure 3 The SEM images of the powders coated with precursors of different concentrations in Example 1 are compared. Figure 4 These are EDS photos of the powder of Example 1 after being coated with precursors at different concentrations. Figure 5 The powder resistivity results of the metallic soft magnetic powder prepared in Example 1 of the present invention at different precursor concentrations. Figure 6 The powder resistivity results of the carbonyl iron powder prepared in Example 3 of the present invention before and after coating. Figure 7 This is a cross-sectional TEM photograph of the coated soft magnetic metal powder prepared in Example 1 of the present invention.

[0131] From Figure 2 It can be seen that there is a layer of coating on the surface of the powder after coating. Figure 3The results show that with the increase of the content of aluminum isopropoxide, the coating layer on the powder surface becomes gradually obvious. Figure 4 The Al and O elements on the powder surface indicate that the powder surface is uniformly coated with Al2O3. Figure 5 The resistivity results show that the insulation properties of the coated powder are significantly improved. The insulation properties of carbonyl iron powder are also improved by applying this method. Figure 6 As shown in the cross-sectional photo of the coating layer, it can be seen that the coating layer on the powder surface is complete and uniform, and the thickness is relatively thin, as shown in the figure. Figure 7 As shown. Figure 8 As shown, Example 8 gives a SEM photo of the coated powder prepared with ethyl orthosilicate as a precursor. Fig. 9 As shown, Example 9 gives the SEM and EDS results of the coated powder prepared with magnesium acetate tetrahydrate as a precursor, both of which show a good coating effect.

[0132] The effective permeability and DC bias performance of the samples of Examples 1, 2, 4 of the present invention and Comparative Example 1 are shown in Table 1; Table 2 shows the power loss (P cv ), it can be seen that the soft magnetic composite material sample prepared by the present invention has relatively low loss characteristics.

[0133] Table 1 Effective permeability and DC bias performance of samples prepared by different processes

[0134]

[0135] Table 2 Power loss (P cv :mW / cm 3 )

[0136]

[0137]

[0138] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A highly efficient chemical liquid phase coating method for metal soft magnetic powder, characterized in that: The method comprises the following steps: Placing the powder to be coated in the reaction chamber, and introducing a fluidizing gas source into the reaction chamber to uniformly fluidize the powder in the reaction chamber; Dissolving a metal compound or an organic compound in a solvent to form a coating precursor solution, spraying the precursor solution into a reaction chamber and allowing the precursor solution to fully react with the powder to be coated to obtain a surface-modified metal soft magnetic powder; calcining the surface-modified soft magnetic powder to obtain a coated magnetic powder with a core-shell structure of the soft magnetic powder, and mixing the coated magnetic powder with a resin binder to form granules and then pressing to obtain a green body of a soft magnetic composite material; The metal soft magnetic composite material green body is subjected to heat treatment, and the metal soft magnetic composite material is obtained after completing heating curing or annealing treatment.

2. The high-efficiency chemical liquid phase coating method for metal soft magnetic powder according to claim 1, characterized in that: The metal compound includes aluminum isopropoxide, pseudo-boehmite white powder, aluminum sec-butoxide, magnesium acetate tetrahydrate or sodium silicate nonahydrate; the organic compound includes ethyl orthosilicate or tetrabutyl titanate; The purity of aluminum isopropoxide, pseudo-boehmite and aluminum sec-butoxide is greater than 99%, and the aluminum content is between 5% and 30%; the purity of ethyl orthosilicate, magnesium acetate tetrahydrate and sodium silicate nonahydrate is greater than 98%.

3. The high-efficiency chemical liquid phase coating method for metal soft magnetic powder according to claim 1, characterized in that: The solvent includes a single organic solvent or a mixed solvent of deionized water, methanol, ethanol, glycerol, isopropanol, and toluene.

4. The high-efficiency chemical liquid phase coating method for metal soft magnetic powder according to claim 1, characterized in that: The metal soft magnetic powder includes at least one of carbonyl iron powder, Fe-Ni-Mo alloy powder, Fe-Ni alloy powder, Fe-Co alloy powder, Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Si-Cr alloy powder, Fe-based amorphous alloy powder, Ni-based amorphous alloy powder, Co-based amorphous alloy powder and Fe-based nanocrystalline powder.

5. The high-efficiency chemical liquid phase coating method for metal soft magnetic powder according to claim 1, characterized in that: The gas flow temperature of the fluidizing gas source is 50°C to 600°C, and the flow rate of the gas flow is 4m 3 / min~50m 3 / min, the air flow speed is 0.4m / s~10m / s.

6. The high-efficiency chemical liquid phase coating method for metal soft magnetic powder according to claim 1, characterized in that: The calcination temperature range is 400° C. to 1000° C., and the calcination time is 1 h to 3 h.

7. The high-efficiency chemical liquid phase coating method for metal soft magnetic powder according to claim 1, characterized in that: The coating precursor solution is drawn into the atomizing device through a suction device, and forms a precursor solution spray after passing through the atomizing device.

8. The high-efficiency chemical liquid phase coating method for metal soft magnetic powder according to claim 7, characterized in that: The rotation speed of the suction device is 2 r / min to 100 r / min, and the air pressure of the atomization device is 0.1 MPa to 10 MPa.

9. Use of the metal soft magnetic composite material obtained by the high-efficiency chemical liquid phase coating method of metal soft magnetic powder according to any one of claims 1 to 8 in an integrally formed inductor or metal soft magnetic powder core.

Citation Information

Patent Citations

  • Metal magnetic powder core and preparation method thereof

    CN113096907A

  • Magnetic powder core and preparation method thereof

    CN115579207A

  • Preparation method of high-frequency iron-silicon soft magnetic composite material

    CN117747280A

  • Fluidized bed spray coating equipment

    CN221951152U

  • Dust core and soft magnetic metal powder therefor

    JP2007194273A

Cited By

  • Device and method for preparing submicron powder with core-shell structure by compounding heat preservation type plasma arc-spray coating

    CN119772189A

  • An apparatus and method for preparing submicron powder with core-shell structure by thermal-insulated plasma arc-spray coating composite

    CN119772189B

  • Method and device for preparing Ti-TiN core-shell powder

    CN120190345A

  • Preparation method of low-oxygen-content metal powder

    CN120394885A

  • A method for preparing metal powder with low oxygen content

    CN120394885B